2019
DOI: 10.20333/2500136-2019-3-24-33
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Composition and Blood Metabolic Profile According to Ab0-System: Grouping, Comparative Description

Abstract: Клиники Самарского государственного медицинского университета, Самара 443079, Российская Федерация Цель исследования. Выявить основные тенденции в распределении групп крови по системам AB0 и Резус в зависимости от возраста, охарактеризовать изменение клеточного состава крови и биохимического профиля, ассоциированного с групповой принадлежностью крови исследуемых лиц. Материал и методы. В исследовании приняли участие 2 группы: контрольная, состоящая из 4988 человек, средний возраст которых составил 34±3 года, и… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…It was found that the incidence of thromboembolic complications in various diseases is associated with blood group affi liation, incidence in "antigenic" blood groups is 30% higher compared to 0 (I) group carriers [24]. This interrelation can also be explained by antigen-mediated change of von Willebrandt factor levels and factor VIII in plasma [6], the lowest content of which is observed in "zero" blood group carriers. Antigens A and B carriers have an elevated content of these factors, contributing to an increased risk of thrombosis, also explaining risk of myocardial ischemia.…”
Section: Non-communicable Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that the incidence of thromboembolic complications in various diseases is associated with blood group affi liation, incidence in "antigenic" blood groups is 30% higher compared to 0 (I) group carriers [24]. This interrelation can also be explained by antigen-mediated change of von Willebrandt factor levels and factor VIII in plasma [6], the lowest content of which is observed in "zero" blood group carriers. Antigens A and B carriers have an elevated content of these factors, contributing to an increased risk of thrombosis, also explaining risk of myocardial ischemia.…”
Section: Non-communicable Diseasesmentioning
confidence: 99%
“…0 (I) blood group carriers are less susceptible to age-related cognitive changes and therefore have longer life expectancy. Another intriguing mechanism may include antiangiogenic properties of von Willebrand factor, explaining a more complete brain vascularization in individuals with group 0 (I), due to the lower content of von To facilitate comprehension of this paper, we will use division of blood groups according to the AB0 system into "zero" group -0 (I), that does not contain antigens A, B, AB and "non-zero", or "antigenic" groups, that correspond to blood groups A (II), B (III), AB (IV) in the generally accepted classifi cation [6].…”
Section: Non-communicable Diseasesmentioning
confidence: 99%
See 1 more Smart Citation